Treatment action campaign : managing activists - Metton, Eulalie (SAGE knowledge. Cases., 2016)
The Treatment Action Campaign (TAC) is widely regarded as one of the most successful HIV/AIDS activist organisations in the world. However, by 2008, the organisation was facing new challenges. This book examines how founder Zackie Achmat and his team prepared TAC to change and adapt its services and operations.